2022
DOI: 10.1002/ab.22019
|View full text |Cite
|
Sign up to set email alerts
|

Capturing mechanisms of change: Weekly covariation in anger regulation, hostile intent attribution, and children's aggression

Abstract: Interventions for children's aggression typically target assumed underlying mechanisms, such as anger regulation and hostile intent attribution. The expectation here is that targeting these mechanisms will result in within-person changes in aggression. However, evidence for these mechanisms is mostly based on between-person analyses. We, therefore, examined whether within-person changes in adaptive anger regulation and hostile intent attribution covaried with within-person changes in children's aggression.Chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 49 publications
(70 reference statements)
2
13
0
Order By: Relevance
“…An intervention with weekly sessions should, in theory, be able to produce weekly changes in these mechanisms. Indeed, a recent study has revealed that weekly changes in adaptive anger regulation and hostile intent attribution covaried with weekly changes in children's aggression (Alsem, Keulen, et al, 2022). The present study builds on these ndings by examining, within an intervention study, whether causing changes in these mechanisms would go together with reductions in children's aggression.…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…An intervention with weekly sessions should, in theory, be able to produce weekly changes in these mechanisms. Indeed, a recent study has revealed that weekly changes in adaptive anger regulation and hostile intent attribution covaried with weekly changes in children's aggression (Alsem, Keulen, et al, 2022). The present study builds on these ndings by examining, within an intervention study, whether causing changes in these mechanisms would go together with reductions in children's aggression.…”
Section: Introductionmentioning
confidence: 75%
“…The psychometric quality of the weekly measures used in the current study were investigated in an earlier study. Results showed adequate internal consistency, convergent, and concurrent validity for the childreport version (Alsem, Keulen, et al, 2022).…”
Section: Methodsmentioning
confidence: 93%
See 1 more Smart Citation
“…Ratings were averaged across items. The child report version of this measure was investigated in another study (n = 223, M age = 10.18, SD = 1.21; (Alsem, Keulen, et al, 2022). Results showed adequate internal consistency (i.e., Cronbach's α's ranged from .64 to .69 over four weeks) and supported the convergent and concurrent validity.…”
Section: Aggressive Behaviormentioning
confidence: 95%
“…To assess weekly change in children's aggression during the treatment, a measure was needed that can be used for such frequently repeated measurements (Lischetzke, 2014). Therefore, we chose to use a new weekly report measure (Alsem, Keulen, et al, 2022). Parents and children rated three items (i.e., 'This week I/my child fought with someone,' 'This week I/my child kicked or beat someone,' and 'This week I/my child called someone names') on a scale from 1 ('never) to 5 ('very often').…”
Section: Aggressive Behaviormentioning
confidence: 99%